Manajemen Kelas dalam Meningkatkan Minat Belajar Peserta Didik di Mts Bina Taruna Jaya Medan - Risa Adela (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The research that has been carried out is entitled "Class Management in Increasing Students' Interest in Learning at MTs Bina Taruna Jaya Medan" which is motivated by the fact that students' interest in learning at MTs Bina Taruna Jaya Medan is an effort to increase students' interest in learning, knowing the supporting factors and hindering factors. Seeing that there are several problems in increasing students' interest in learning in class, including students who are not enthusiastic about participating in learning. Students who are mostly silent give the impression that they are not involved or active in the learning process, students are constantly chatting alone with their friends. This research was conducted using a qualitative descriptive research method, namely providing a more detailed description of the research object sourced from primary and secondary data. The data collection techniques used were observation, interviews and documentation. The instrument in this research uses interviews in the form of guidelines consisting of several questions. The results of this research show that Class Management in Increasing Students' Interest in Learning at MTs Bina Taruna Jaya Medan has been implemented well by the homeroom teacher, subject teachers, principal and students by using class management strategies, namely creating a conducive classroom atmosphere, providing motivation and directions so that students care about the cleanliness of the room, visit the class to organize the room, guide students in the learning process. The supporting and inhibiting factors are supporting facilities and infrastructure, the availability of equipment such as blackboards which are said to be suitable, the availability of a library in each class, Based on the research findings above, the learning approach must be suitable for implementation by students, teachers and school principals as a solution to create quality learning in classroom management to increase students' interest in learning.